Severe Post-Viral Polymyositis after COVID-19 in Childhood: A Case Report and Literature Review - Jurgita Marciulynaite; Rima Sileikiene; Ausra Snipaitiene (MDPI AG, 2024)
Polymyositis is a rarely reported complication of COVID-19 illness, especially in children. Molecular mimicry may be a cause of hyperactivated autoimmunity, leading to various clinical manifestations, including myopathies. Symptoms vary from mild muscle weakness to severe rhabdomyolysis. We review the literature on post-COVID myositis and report a case of severe polymyositis in a 7-year-old boy, following undefined viral infection 3 weeks before the onset of muscle pain. Patient's condition deteriorated from physical activity-associated pain in the lower limbs to severe muscle weakness leading to dysphagia and mechanical ventilation. As antibodies against SARS-CoV-2 were detected and other possible conditions causing myositis were excluded, the diagnosis of post-COVID polymyositis was considered as the most likely. The patient was treated with high doses of methylprednisolone and cyclophosphamide, resulting in improvement. Although COVID-19 is becoming a seasonal disease, the infection itself and post-viral disorders, such as polymyositis, are still of great interest and require better investigation to ensure appropriate management for each individual. Our experience suggests that aggressive immunosuppressive therapy might be a solution for severe post-COVID-related diseases. This literature review is provided in addition to the case report presented at the 29th European Paediatric Rheumatology Congress; the abstract is available online in the Proceedings of the 29th European Paediatric Rheumatology Congress.